THE CULTURAL-ACADEMIC GAPS FACED BY THE EFL LEARNERS IN UNDERSTANDING AND USING ENGLISH TENSES - Jufrizal Jufrizal; Lely Refnita (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2013)
That there are many grammatical features of English which are different from those of bahasa Indonesia and of other local languages in Indonesia should be academically and culturally understood by EFL learners in Indonesia. Most EFL learners say that they have known grammatical features and functions concerning with the English tenses, but some facts tell that they fail to use the appropriate tenses in speaking and in writing short texts. This condition was found at the English Department of FKIP Universitas Bung Hatta, Padang. This paper discusses the cultural-academic gaps commonly faced by the EFL learners at the English Department of FKIP Universitas Bung Hatta, Padang. The discussion of this paper is based on the questions: (i) what are the grammatical problems made by the English Department students of FKIP Universitas Bung Hatta in writing essays concerning with the use of English tenses?; (ii) do they face cultural and academic gaps in understanding and using the English tenses appropriately?; and (iii) why do they face such cultural and academic gaps? The data and discussion presented in this paper are based on the results of pre-research conducted on January 2012, as a part of stages of a Research and Development (R & D) conducted at the English Department of FKIP Universitas Bung Hatta, Padang. Key words/phrases: English, grammar, tenses, EFL learners, cultural gaps, academic gaps